Monitoring Tegangan Aki Kendaraan Berbasis Smartphone Android - Nujkhan Tamara; Wahyu Sapto Aji (Buletin Ilmiah Sarjana Teknik Elektro, 2021)
The existence of a battery is very helpful for motorized vehicles to supply electrical power to the electrical components of a motorcycle. As long as the battery is used, sometimes there are problems, namely the ignorance of motorized vehicle users when the battery condition is at a voltage level below the average of 85%, in dry batteries the recommended minimum voltage is 10.5 Volts. This study intends to solve this problem by designing an IoT-based battery current and voltage monitoring system. A tool to monitor the condition of the current and voltage of a motor vehicle battery can be done using the IOT (Internet of Things) monitoring system on an android smartphone. This tool contains components such as Arduino Uno R3 board, voltage sensor, current sensor, ESP8266 wifi module and power supply. The measured data is sent via the internet network, the interface uses an android smartphone and the data is displayed using the ThingView application. The device can monitor battery current and voltage. The battery current and voltage data has been successfully read and sent to the user, the idling data is -0.609 A and 14.82 V, the average rotation data is -0.792 A and 15.042 V, and the high rotation data is -0.861 A and 15.319 V. Keberadaan aki sangat membantu kendaraan bermotor untuk menyuplai daya listrik menuju komponen listrik sepeda motor. Selama aki digunakan terkadang menemukan masalah yaitu ketidaktahuan pengguna kendaraan bermotor saat kondisi aki telah berada pada level tegangan dibawah rata-rata 85%, pada aki kering tegangan minimal yang disarankan sebesar 10,5 Volt. Penelitian ini bermaksud memecahkan masalah ini dengan mendesain sistem monitoring arus dan tegangan aki berbasis IoT. Alat untuk memantau kondisi arus dan tegangan aki kendaraan bermotor dapat dilakukan menggunakan sistem monitoring IOT (Internet of Things) pada smartphone android. Alat ini mengandung komponen berupa board arduino uno R3, sensor tegangan, sensor arus, modul wifi ESP8266 dan catu daya. Data yang terukur dikirim melalui jaringan internet, antarmuka menggunakan smartphone android dan data ditampilkan menggunakan aplikasi ThingView. Piranti dapat memantau arus dan tegangan aki. Data arus dan tegangan aki berhasil dibaca dan dikirm ke pengguna, data saat langsam sebesar rerata -0,609 A dan 14,82 V, data saat rotasi sedang sebesar rerata -0,792 A dan 15,042 V, serta data saat rotasi tinggi sebesar rerata -0,861 A dan 15,319 V.